Comparative Analysis of Glycosidic Aroma Compound Profiling in Three Vitis vinifera Varieties by Using Ultra-High-Performance Liquid Chromatography Quadrupole-Time-of-Flight Mass Spectrometry - Wei, Yi; Chen, Zhuo; Zhang, Xin-Ke; Duan, Chang-Qing; Pan, Qiu-Hong (Frontiers in Plant Science, 2021)
Glycosidic aroma compounds are the important precursors of volatile aroma in grapes, and they can be added with odorous aglycones via enzyme- or acid-catalyzed hydrolysis during wine fermentation and storage. Developing an analytical method for intact glycosides can provide the possibility to study the accumulation of these aroma precursors in grape berries. For this purpose, a Tandem Mass Spectrometry (MS/MS). database based on ultra-high-performance liquid chromatography quadrupole-time-of-flight mass spectrometry was built, covering multiple aglycone classes. Subsequently, the profiles of glycosidic aroma compounds in Vitis vinifera L. cv. Muscat Blanc, Riesling, and Chardonnay berries during maturation were investigated. Pentosyl-hexosides were the most abundant glycosides in all three varieties. Both composition and concentration of glycosidic aroma compounds varied obviously among grape varieties. Except for monoterpenol pentosyl-hexosides, most glycosides were kept almost stable in their concentrations during berry maturation. This research provides an approach to understand the variation of glycosidic aroma components from the perspective of aglycones and glycosides.